Youth violence intervention programme for vulnerable young people attending emergency departments in London: a rapid evaluation - Appleby John; Georghiou Theo; Ledger Jean; Rolewicz Lucina; Sherlaw-Johnson Chris; Tomini Sonila M; Frerich Jason M; Ng Pei Li (NIHR Journals Library, 2023)
Background Youth violence intervention programmes involving the embedding of youth workers in NHS emergency departments to help young people (broadly aged between 11 and 24 years) improve the quality of their lives following their attendance at an emergency department as a result of violent assault or associated trauma are increasing across the NHS. This study evaluates one such initiative run by the charity Redthread in partnership with a NHS trust. Objectives To evaluate the implementation and impact of a new youth violence intervention programme at University College London Hospital NHS Trust and delivered by the charity Redthread: (1) literature review of studies of hospital-based violent crime interventions; (2) evaluation of local implementation and of University College London Hospital staff and relevant local stakeholders concerning the intervention and its impact; (3) assessment of the feasibility of using routine secondary care data to evaluate the impact of the Redthread intervention; and (4) cost-effectiveness analysis of the Redthread intervention from the perspective of the NHS. Methods The evaluation was designed as a mixed-methods multiphased study, including an in-depth process evaluation case study and quantitative and economic analyses. The project was undertaken in different stages over two years, starting with desk-based research and an exploratory phase suitable for remote working while COVID-19 was affecting NHS services. A total of 22 semistructured interviews were conducted with staff at Redthread and University College London Hospital and others (e.g. a senior stakeholder involved in NHS youth violence prevention policy). We analysed Redthread documents, engaged with experts and conducted observations of staff meetings to gather more in-depth insights about the effectiveness of the intervention, the processes of implementation, staff perceptions and cost. We also undertook quantitative analyses to ascertain suitable measures of impact to inform stakeholders and future evaluations. Results Redthread's service was viewed as a necessary intervention, which complemented clinical and other statutory services. It was well embedded in the paediatric emergency department and adolescent services but less so in the adult emergency department. The diverse reasons for individual referrals, the various routes by which young people were identified, and the mix of specific support interventions provided, together emphasised the complexity of this intervention, with consequent challenges in implementation and evaluation. Given the relative unit costs of Redthread and University College London Hospital's inpatient services, it is estimated that the service would break even if around one-third of Redthread interventions resulted in at least one avoided emergency inpatient admission. This evaluation was unable to determine a feasible approach to measuring the quantitative impact of Redthread's youth violence intervention programme but has reflected on data describing the service, including costs, and make recommendations to support future evaluation. Limitations The COVID-19 pandemic severely hampered the implementation of the Redthread service and the ability to evaluate it. The strongest options for analysis of effects and costs were not possible due to constraints of the consent process, problems in linking Redthread and University College London Hospital patient data and the relatively small numbers of young people having been engaged for longer-term support over the evaluation period. Conclusions We have been able to contribute to the qualitative evidence on the implementation of the youth violence intervention programme at University College London Hospital, showing, for example, that NHS staff viewed the service as an important and needed intervention. In the light of problems with routine patient data systems and linkages, we have also been able to reflect on data describing the service, including costs, and made recommendations to support future evaluation. Future work No future work is planned. Funding National Institute for Health and Care Research Health Services and Delivery Research programme (RSET: 16/138/17). Plain language summary Youth violence intervention programmes in the NHS embed specialist youth workers into a hospital's paediatric emergency departments. These staff can engage young people and encourage positive change in their lives. Youth violence intervention programmes are part of a broader national strategy to prevent violence among young people. To improve our knowledge of the impact on young people and the cost-effectiveness of youth violence intervention programmes, we carried out an evaluation of a youth violence intervention programme introduced in 2020 at University College London Hospital and run by the charity Redthread. We reviewed the international evidence on youth violence intervention programmes, and other studies of Redthread services but found few studies measuring impact within the NHS. We reviewed documents and conducted 22 interviews with University College London Hospital and Redthread staff among others. We found that the service is viewed positively by NHS staff. We also found that youth workers can help a young person to better engage in their medical care and treatment. Youth violence intervention programmes also provide a link with non-health-care services within the community. Overall, they help NHS staff to better support vulnerable young people following discharge from hospital. We also established the cost of delivering Redthread services per user was £1865. This compares with a cost per inpatient of £5789 for a group of patients similar to those helped by Redthread. The average cost of a Redthread-type patient attending the emergency department was £203. We looked at whether it was possible to measure whether Redthread reduced young people's re-admissions to the hospital's emergency departments. However, we concluded that fully answering this question was not possible over the timescale of the project. This was because of the impact of COVID-19 on Redthread and other paediatric services, the low numbers of young people engaged in a longer-term programme with Redthread (59) and difficulties with linking information from the hospital and Redthread. We have therefore made various recommendations in this report to improve the way that data are collected and linked to aid future evaluations. Scientific summary Background Youth violence intervention programmes (YVIPs), and in particular those based in emergency departments (EDs), aimed broadly at young people aged between 11 and 24 years of age are part of a wider national strategy to tackle violence, the risk of violence or other types of harm. Despite many such programmes there is limited knowledge about their impact and cost-effectiveness. Prior attempts to demonstrate the efficacy of ED-based programmes have also been underpowered and results have been largely equivocal. Redthread has been implementing YVIPs in hospitals since 2006. In 2020, they started a service at University College London Hospitals NHS Trust (UCLH). This programme embeds specialist youth workers into some of the trust's clinical departments, capitalising on 'teachable moments' to engage young people and encourage positive change in their lives.